High‐Rate, Tunable Syngas Production with Artificial Photosynthetic Cells. (30th April 2019) - Zhang, Hongwen; Ming, Jintao; Zhao, Jiwu; Gu, Quan; Xu, Chao; Ding, Zhengxin; Yuan, Rusheng; Zhang, Zizhong; Lin, Huaxiang; Wang, Xuxu; Long, Jinlin
Abstract: An artificial photosynthetic (APS) system consisting of a photoanodic semiconductor that harvests solar photons to split H2 O, a Ni‐SNG cathodic catalyst for the dark reaction of CO2 reduction in a CO2 ‐saturated NaHCO3 solution, and a proton‐conducting membrane enabled syngas production from CO2 and H2 O with solar‐to‐syngas energy‐conversion efficiency of up to 13.6 %. The syngas CO/H2 ratio was tunable between 1:2 and 5:1. Integration of the APS system with photovoltaic cells led to an impressive overall quantum efficiency of 6.29 % for syngas production. The largest turnover frequency of 529.5 h −1 was recorded with a photoanodic N‐TiO2 nanorod array for highly stable CO production. The CO‐evolution rate reached a maximum of 154.9 mmol g −1 h −1 in the dark compartment of the APS cell. Scanning electrochemical–atomic force microscopy showed the localization of electrons on the single‐nickel‐atom sites of the Ni‐SNG catalyst, thus confirming that the multielectron reduction of CO2 to CO was kinetically favored. Abstract : Hell und dunkel : Die Integration eines künstlichen Photosynthesesystems in Photovoltaikzellen führt zu einer solarbetriebenen Synthesegasproduktion mit einem Gesamtwirkungsgrad von 6.29 %. Die von der Photoanode geernteten Solar‐Photonen zerlegen H2 O, und die Ni‐Zentren in der Kathode katalysierten die CO2 ‐Reduktion, resultierend in einem Solar‐zu‐Synthesegas‐Wirkungsgrad von bis zu 13.6 % (siehe Bild).